The spatial orientation of crista ampullaris: implications for BPPV diagnosis and treatment - Zhou, Mi; Mao, Jiesheng; Yang, Xiaokai (Frontiers in Neurology, 2024)
Objective: This study aimed to provide a comprehensive understanding of the spatial orientation of the crista ampullaris within the inner ear and its implications for the diagnosis and management of benign paroxysmal positional vertigo (BPPV). Methods: Using micro-CT scans of normal human temporal bones, 3D models of the semicircular canals and the eyeballs were segmented. The spatial coordinate system was established by taking the top of the common crus and the bottom of the eyeballs as the horizontal plane. With this calibrated reference system, the orientations of the crista ampullaris were quantified by calculating the angles between the defined crista planes and the coordinate planes. Results: The plane of the ampulla and the corresponding semicircular canal plane are nearly perpendicular to each other. In the upright position, the posterior semicircular canal crista ampullaris formed an angle of 48.9° with the horizontal plane. The relative orientations of the crista ampullaris of the lateral and superior canals were also defined. Furthermore, we identified "zero-point planes" representing crista orientations perpendicular to gravity, which resulted in minimal ampullary stimulation. A 6.2° tilt to the left in the supine position resulted in the plane of the left lateral semicircular canal crista ampullaris being parallel to the direction of gravity. Conclusion: This study elucidates the precise spatial orientation of the crista ampullaris, thereby providing an anatomical basis for understanding BPPV pathophysiology and improving the accuracy of diagnostic and therapeutic maneuvers. The findings have the potential to significantly enhance the management of BPPV and other inner ear disorders.